(untitled) - Woods, Ilene; 1890-1966.; Felton, Verna; Audley, Eleanor; Luske, Hamilton S.; Sharpsteen, Ben.; Geronimi, Clyde; Peet, Bill (Distributed by Buena Vista Home Entertainment, 2005)
Cinderella has faith her dreams of a better life will come true. With help from her loyal mice friends and a wave of her Fairy Godmothers wand, Cinderellas rags are magically turned into a glorious gown, and off she goes to the Royal Ball. But when the clock strikes midnight, the spell is broken, leaving only a single glass slipper, the only key to the ultimate fairy-tale ending! Bonus features included.
CHV rating: G.
MPAA rating: G
Keywords: Cinderella; (Legendary character); Juvenile drama; Balls (Parties); Juvenile drama; Fairy tales; Juvenile drama; Stepchildren; Juvenile drama; Stepsisters; Juvenile drama; Princesses; Juvenile drama; Princes; Juvenile drama; Video recordings for the hearing impaired; Animated films; Childrens films